ANALYSIS OF THE INFLUENCE OF RELIEF ON THE CHOICE OF TRANSPORT FOR TRANSPORTING ORE FROM THE ORE STORAGE HOUSE OF THE "SKIPOVOY" STOVOLY, LOCATED IN THE ZARMITAN GOLDEN MINE ZONE, TO THE 4-GMZ ORE STORAGE HOUSE (Web of Teachers: Inderscience Research, 2025)
In modern global and national economic conditions, the efficiency of extracting and processing technological gold-bearing ore deposits is being improved through the integration of mining teams and processing enterprises into powerful structural units. These formations enable the complex development of deposits. The optimization of ore flows and evaluation of ore quality enhancement methods require scientific justification tailored to the specific conditions of each mining enterprise. However, the theoretical foundations and technologies for extracting polymetallic and complex ores remain insufficiently developed, particularly in the context of current economic demands. A deeper understanding of the interdependence between geological data reliability, exploration, enrichment, and market processes is essential for forming cost-effective technological schemes. The optimal use of transport systems in mining is determined by technical parameters, terrain constraints, and logistical factors. This paper considers the example of the Zarmitan deposit, presenting transport layouts and operational plans for enhancing ore delivery efficiency.